Working Behind Bars, General Rules For Penitentiary Employees : Array - Proca, Florin (Journal of Danubian Studies and Research, 2021)
At first glance, working in a penitentiary unit seems quite simple: the employees provides security, accommodation, food, hygiene items, clothing when needed and the possibility of daily recreation for the imprisoned persons and inmates are waiting for the time to re-enter the society. In fact, things are much more complex. The objective of the research is to identify the problems faced by prison staff, other than those clearly regulated by the normative acts as well as to establish the manner of action in case of such difficult situations. I approached this topic because it is of interest both to the new staff employed in such a complex and stressful institution and to the long-term employees in this field. In this "gray" environment, which is in a continuous tension and transformation, new situations always appear that initially seem impossible to solve, situations whose solution is not specified in laws or regulations. Prisons and convicts have been a topic of great interest recently, both in the media and in the legislation, where many changes have taken place for the benefit of persons deprived of their freedom. All this has overshadowed the other human element of the prison environment - the prison staff, which in addition to working in a very dangerous environment and sometimes have to manage people who have nothing to lose, also face the feeling of social isolation due to the numerous restrictions that come with choosing this profession. The long-term negative effects of working with inmates, as well as the unwanted habits that the employees involuntarily acquire due to the nature of the job, should not be neglected, but rather studied and stopped as much as possible.